Ungkapan Verbal dan Non Verbal Bermakna Budaya - Longdong, Wingston M.J (Universitas Sam Ratulangi, 2015)
This study deals with the Antropholinguistic appaoach of Tonsea Language,especially expressions used verbally or non verbally in the ceremony of Maator Mbanua. The aim of this study is to identity and describe those two kinds of expressions which are deal with cultural meaning, and try to find and analyzeit, in order to increase and develop the language and culture of Tonsea.Â Keywords : Verbal and NonVerbal expressions, language and culture.